2018
DOI: 10.1167/iovs.18-24348
|View full text |Cite
|
Sign up to set email alerts
|

Outer Plexiform Layer Elevations as a Marker for Prior Ocular Attacks in Patients With Behcet's Disease

Abstract: METHODS. Thirty-one consecutive patients (59 eyes) with Behcet's disease in remission and with available optical coherence tomography (OCT) images were included. The number of OPL bumps was counted using spectral-domain OCT images. The relationships between the number of bumps and visual acuity (VA), retinal thickness, choroidal thickness, disease duration, number of prior ocular attacks, and photoreceptor layer status (including external limiting membrane [ELM] and ellipsoid zone [EZ] continuity) were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…,), and which were also recently identified as being associated with Behcet's disease (Kido et al. ). Finally, in one patient with multiple bilateral resolved PAMM lesions, we observed the evolution of an acute hyperreflective lesion at the level of INL to a focal outer plexiform layer elevation similar to the evolution of the acute PAMM lesion (Nemiroff et al.…”
Section: Discussionmentioning
confidence: 86%
“…,), and which were also recently identified as being associated with Behcet's disease (Kido et al. ). Finally, in one patient with multiple bilateral resolved PAMM lesions, we observed the evolution of an acute hyperreflective lesion at the level of INL to a focal outer plexiform layer elevation similar to the evolution of the acute PAMM lesion (Nemiroff et al.…”
Section: Discussionmentioning
confidence: 86%
“…Similar to previous studies, we observed the localized RNFL defects identified by Oray et al, 21 which indicate the previous inflammatory episodes, were displayed as hypoperfused-nonperfused areas by OCTA. 12 OPL defects, which were reported by Kido et al 22 and were suggested as a marker for the previous uveitis episodes, were also examined. Hypoperfusionnonperfusion areas corresponding to these defects were determined with OCTA especially in DCP.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, OCT is a non-invasive tool used to visualize the fundus. Furthermore, OCT can provide useful markers of previous posterior ocular flares such as outer plexiform layer elevations associated with focal inner nuclear layer collapse (Figure 4) [27]; this could help with retrospective diagnosis in case of clinical suspicion. As described above, BD uveitis diagnosis is usually established in the presence of a coherent ocular clinical presentation and extraocular manifestations according to classification criteria.…”
Section: Strategy For Definite and Earlier Diagnosis Of Behçet's Disease Uveitismentioning
confidence: 99%
“…In contrast, OCT is a non-invasive tool used to visualize the fundus. Furthermore, OCT can provide useful markers of previous posterior ocular flares such as outer plexiform layer elevations associated with focal inner nuclear layer collapse (Figure 4) [27]; this could help with retrospective diagnosis in case of clinical suspicion. A more recent technology, Enhanced Depth Imaging OCT (EDI-OCT) provides detailed and measurable images from the choroid.…”
Section: Strategy For Definite and Earlier Diagnosis Of Behçet's Disease Uveitismentioning
confidence: 99%